Education service delivery: the disastrous case of outcomes-based qualifications frameworks - Allais, Stephanie Matseleng (SAGE Publications, 2007)
International trends towards outcomes-based qualifications frameworks as the drivers of educational reform fi t in well with trends in service delivery and public sector reform. Education reform in South Africa provides a particularly interesting case study of this phenomenon, because of the very comprehensive outcomes-based national qualifications framework that was implemented shortly after the transition to democracy. Problems with the framework as a basis for education reform became rapidly apparent, and the system is now deadlocked in a series of unresolved policy reviews. A key to understanding this collapse is the role of knowledge in relation to education. The outcomes based qualification framework approach turns out to have very little to do with education, and in fact to have the potential to increase educational inequalities, particularly in poor countries.
Keywords: Outcomes-based education; National qualifications framework; Qualification-driven reform; Education service delivery; South Africa